Peningkatan Rasa Nasionalisme di Kalangan Generasi Muda Melalui Pendidikan Kewarganegaraan - Widya Utami; Diva Pasanta Diani; Harlian Satria Wilwatikta; Falah Al Ghozali (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
At this time the development of Indonesian society and the development of Indonesian law has undergone significant changes which also affect the nation's sense of nationalism. The current millennial generation has experienced a collapse of rationalism where this has occurred by the erosion of the values of nationalism of the younger generation which is the basis of the younger generation's love for their homeland Indonesia. Many young people do not understand the essence of the implementation of nationalism. The spirit of the previous generation of young people who had a fighting spirit and a high spirit of nationalism, is now slowly fading. In the journey of the Indonesian state, it has been proven that youth has a significant role to be able to become an agent of change from a country colonized by the Dutch by means of colonization to a conducive country. Basically, Indonesian youth have the intelligence to think openly and tolerantly to accept differences (diversity) in race, ethnicity, religion and culture. Nationalism is a vehicle capable of mobilizing elements of society and eliminating the influence of bad foreign cultures and aims to revive a culture that reflects the nation's pride. The substance of Indonesian Nationalism has two elements, first, public awareness of the importance of units and also the unity of the Indonesian nation consisting of tribes, ethnicities, and religions. Secondly, the awareness of the Indonesian people in the elimination of all foreign cultures. The influx of outside cultures has a major impact on the erosion of the sense of nationalism of Indonesia's young generation today. In addition to the influence of external cultures that arise, the influence of the government also has an impact on the waning sense of nationalism of the nation's children